Analysis of the Use of Extracorporeal Circulation on the In-Hospital Outcomes of Dialytic Patients Who Underwent Myocardial Revascularization Surgery - Miranda,Matheus (2016)
Abstract Background: Myocardial revascularization surgery is the best treatment for dyalitic patients with multivessel coronary disease. However, the procedure still has high morbidity and mortality. The use of extracorporeal circulation (ECC) can have a negative impact on the in-hospital outcomes of these patients. Objectives: To evaluate the differences between the techniques with ECC and without ECC during the in-hospital course of dialytic patients who underwent surgical myocardial revascularization. Methods: Unicentric study on 102 consecutive, unselected dialytic patients, who underwent myocardial revascularization surgery in a tertiary university hospital from 2007 to 2014. Results: Sixty-three patients underwent surgery with ECC and 39 without ECC. A high prevalence of cardiovascular risk factors was found in both groups, without statistically significant difference between them. The group "without ECC" had greater number of revascularizations (2.4 vs. 1.7; p <0.0001) and increased need for blood components (77.7% vs. 25.6%; p <0.0001) and inotropic support (82.5% vs 35.8%; p <0.0001). In the postoperative course, the group "without ECC" required less vasoactive drugs, (61.5% vs. 82.5%; p = 0.0340) and shorter time of mechanical ventilation (13.0 hours vs. 36,3 hours, p = 0.0217), had higher extubation rates in the operating room (58.9% vs. 23.8%, p = 0.0006), lower infection rates (7.6% vs. 28.5%; p = 0.0120), and shorter ICU stay (5.2 days vs. 8.1 days; p = 0.0054) as compared with the group with ECC surgery. No difference in mortality was found between the groups. Conclusion: Myocardial revascularization with ECC in patients on dialysis resulted in higher morbidity in the perioperative period in comparison with the procedure without ECC, with no difference in mortality though.